Vitiligo: analysis of grafting versus curettage alone, using melanocyte morphology and reverse transcriptase polymerase chain reaction for tyrosinase mRNA - Machado Filho, Carlos D’Aparecida dos Santos; Almeida, Fernando Augusto; Proto, Rodrigo Sestito; Landman, Gilles (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Recent studies have indicated that vitiligo areas contain inactive or dormant melanocytes. Melanin synthesis is related to tyrosinase presence and indicative of active metabolic state. The aim of this study was to compare repigmentation, epidermal melanocyte distribution and tyrosinase mRNA detection through reverse transcriptase polymerase chain reaction, in tissue samples of vitiligo, before and after curettage, with or without subsequent autologous skin graft using a new method. DESIGN AND SETTING: Prospective, in the Department of Dermatology, Faculdade de Medicina do ABC, Santo André. METHODS: Two vitiligo areas were curetted. One subsequently received grafted normal sacral autologous skin, whereas the other had no further treatment. The curetted areas were examined after 30 days, to evaluate the degree of repigmentation. The melanocyte percentages and tyrosinase mRNA presence in normal skin and vitiligo areas, before and after curettage and grafting, were compared. RESULTS: Complete repigmentation was seen in all grafted areas, whereas non-grafted curetted vitiligo presented partial repigmentation. The me- lanocyte percentage in grafted areas was greater than in non-treated vitiligo skin (p = 0.01) and skin with curettage alone (p = 0.015). Tyrosinase mRNA was negative in 93.75% of non treated vitiligo areas. After treatment (curettage alone or curettage and grafting), all lesions became positive for tyrosinase mRNA. CONCLUSION: Metabolically inactive or dormant melanocytes are probably present within vitiligo areas, and may be activated by exogenous or endogenous stimuli.